Five Facts about the Distributional Income Effects of Monetary Policy - Niklas Amberg; Thomas Jansson; Mathias Klein; Anna Rogantini Picco (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We use Swedish administrative individual-level data to document five facts about the distributional income effects of monetary policy. (i) The effects of monetary policy shocks are U-shaped with respect to the income distribution—i.e., expansionary shocks increase the incomes of high- and low-income individuals relative to middle-income individuals. (ii) The large effects in the bottom are accounted for by the labor-income response and (iii) those in the top by the capital-income response. (iv) The heterogeneity in the labor-income response is due to the earnings heterogeneity channel, whereas (v) that in the capital-income response is due to the income composition channel.
Keywords: C55; E32; E52; 330; monetary policy; income inequality; heterogeneous agents; administrative data